Salvianolic Acid B Restored Impaired Barrier Function via Downregulation of MLCK by microRNA-1 in Rat Colitis Model - Xiong, Yongjian; Wang, Jingyu; Chu, Hongwei; Chen, Dapeng; Guo, Huishu (Frontiers in Pharmacology, 2016)
Salvianolic acid B (Sal B) is isolated from the traditional Chinese medical herb Salvia miltiorrhiza and is reported to have a wide range of therapeutic benefits. The aim of this study was to investigate the effects of Sal B on epithelial barrier dysfunction in rat inflammatory bowel disease (IBD) and to uncover related mechanisms. Rat IBD model was established by intracolonic administration of 2, 4, 6-trinitrobenzene sulfonic acid (TNBS). The intestinal barrier function was evaluated by measuring the serum recovery of ﬂuorescein isothiocyanate-4 kD dextran in vivo and transepithelial electrical resistance in vitro respectively. The protein expression related to intestinal barrier function was studied using western blotting. Besides, the effects of Sal B on inflammatory responses, oxidative damage and IBD recurrence were also studied in this study. The intestinal barrier dysfunction in IBD was reversed by Sal B, accompanied with the decrease of tight junction proteins, and the effect could be blocked by microRNA-1(miR-1) inhibition. The inflammatory responses, oxidative damage and IBD recurrence were also decreased by Sal B. The IBD symptoms and recurrences were ameliorated by Sal B, and restoration of impaired barrier function via dowunregulation of MLCK by miR-1 maybe involved in this effect. This study provides some novel insights into the both of the pathological mechanisms and treatment alternatives of IBD.